2008
DOI: 10.1002/anie.200703612
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Olefins as Steering Ligands in Asymmetric Catalysis

Abstract: Metal-catalyzed asymmetric processes offer one of the most straightforward ways to introduce stereogenic centers. Hence, the development of novel chiral ligands that can effectively induce asymmetry in reactions is crucial in modern organic synthesis. While many established chiral ligands bind to a metal through heteroatoms, structures that coordinate to metals through carbon atoms have received little attention so far. Here, we highlight the increasing number of such chiral chelating olefin ligands as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
219
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(222 citation statements)
references
References 189 publications
3
219
0
Order By: Relevance
“…399 Seminal DFT studies by Qin and Kantchev 400−402 as well as by Brown and Hayashi 403 reported that the conjugate 1,4-addition is thermodynamically preferred over direct 1,2-addition. Moreover, carborhodation was identified as the enantiodetermining step in contrast to previous proposals on enone binding being enantiodiscriminating.…”
Section: Conjugate Additionmentioning
confidence: 98%
“…399 Seminal DFT studies by Qin and Kantchev 400−402 as well as by Brown and Hayashi 403 reported that the conjugate 1,4-addition is thermodynamically preferred over direct 1,2-addition. Moreover, carborhodation was identified as the enantiodetermining step in contrast to previous proposals on enone binding being enantiodiscriminating.…”
Section: Conjugate Additionmentioning
confidence: 98%
“…Independently, Carriera and coworkers reported the application of a chiral diene for Ir-catalyzed allylic substitution [105]. These independent discoveries have spurred intense research efforts in homogeneous catalysis which were compiled in 2008 in an excellent review by Carreira and Grützmacher [106]. An examination of the substituent-effect in chiral bicyclo[2 : 2 : 1]heptadiene scaffold revealed that just two methyl groups in ligand L27a are sufficient to impart a high enantioselectivity (95% ee) in the ECA reaction [99].…”
Section: Diene Ligandsmentioning
confidence: 99%
“…[2] In striking contrast, the relevant palladium(II)-catalyzed alkoxycarbonylation of organoboron compounds has remained far less explored, although other palladium-catalyzed transformations of organoboron species such as SuzukiMiyaura and relevant couplings [3] or other reactions [4] have been extensively developed. [5] There exist only few reports on the methoxycarbonylation of vinyland arylboron reagents. [6,7] Miyaura and Suzuki reported for the first time that alkenylborons derived from the hydroboration of alkynes with catecholborane could be transformed into the corresponding methyl acrylates via palladium-catalyzed methoxycarbonylation at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%